An Analysis of English Speaking Practice through Online Learning for Students (Case Study to The Students Majoring in Management Class 64.1H.05 and 64.1G.05 Kaliabang Branch University of Bina Sarana Informatika) - Arrizqi Ramadhan (Universitas Veteran Bangun Nusantara, 2021)
An Analysis of English Speaking Practice through Online Learning for Students: Practicing English speaking is always necessary for students to communicate globally. In this COVID-19 pandemic, the online learning is the only way for students to still receive the learning process. Students often find the difficulties when studying through online learning, especially when they practice their English speaking. Therefore, the researcher is interested in discussing about the process ofEnglish Speaking Practice through Online Learning, the supporting and obstacling factors. This research would help the lecturers in finding the right methods and teaching techniques, the institution to find and solve the problem and the students to improve their English speaking skills. The researcher will use a descriptive qualitative method. The qualitative research metod is aimed to find the best of an individual point of view and know more about the research in further ways. The researcher will give the quesioner to the respondents and an interview to some of the class representatives.